1991
DOI: 10.1128/aac.35.2.220
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and antibacterial efficacy of cefpirome (HR 810) in experimental Escherichia coli and Haemophilus influenzae type b meningitis

Abstract: Cefpirome (HR 810) is a new cephalosporin related to cefotaxime that has potent bactericidal activity against a broad spectrum of gram-negative and gram-positive organisms. The pharmacokinetics and bacteriological efficacy of cefpirome administered as a single intravenous dose were assessed in rabbits with experimental Haemophilus influenzae type b and Escherichia coli Kl meningitis. The mean penetrations into the cerebrospinal fluid (CSF) in relation to the amount of drug in serum of animals infected with H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Experimental meningitis model. We used our well-characterized meningitis model (9,10,12,18), modified from the original description of Dacey and Sande (2). CSF samples (100 to 200 l) were withdrawn before and at 5, 10, and 24 h after the antibiotic was given.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental meningitis model. We used our well-characterized meningitis model (9,10,12,18), modified from the original description of Dacey and Sande (2). CSF samples (100 to 200 l) were withdrawn before and at 5, 10, and 24 h after the antibiotic was given.…”
Section: Methodsmentioning
confidence: 99%
“…The well-characterized rabbit meningitis model (17,21,24,32), modified from the original description of Dacey and Sande (9), was used. Briefly, New Zealand White male rabbits weighing 2 to 2.5 kg were intramuscularly anesthetized with ketamine (40 mg/kg of body weight) and acepromazine (3 mg/kg) before each procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Cefpirome is a semisynthetic cephalosporin; its in vitro and in vivo activities in animal models, and pharmacokinetic properties, have been evaluated (Ansorg et al 1990;Arai & Hayashi 1990;Bakhtiar & Selwyn 1989;Bertram et al 1984;Clarke et al 1985;Eng et al 1989;Jafari et al 1991;Jones et al 1991;Kavi et al 1989;King et al 1990;KIesel et al 1990;Pucci et al 1991;Sapico et al 1991;Saxby et al 1990;Valdes et al 1 990a). These studies have shown that cefpirome is stable against the action of many fj-lactamases and that it has an improved pharmacokinetic profile compared with most of the existing cephalosporins, excellent in vitro activity against commonly isolated bacterial pathogens, and is effective in eradicating serious infections in experimental animals.…”
Section: Discussionmentioning
confidence: 99%